Successful termination of a multi-year wastewater-associated outbreak of NDM-5-carrying E. coli in a hemato-oncological center - Heidrun Kerschner; Linda Jernej; Adriana Cabal; Patrick Hyden; Sigrid Machherndl-Spandl; Lucia Berning; Anna Blaimschein; Werner Ruppitsch; Petra Apfalter; Rainer Hartl (Antimicrobial Resistance and Infection Control)
Abstract Background In May 2018, an outbreak of NDM-5-carrying Escherichia coli (NDM-5-EC) was detected at the hemato-oncology department of a tertiary care center in Austria. This report details the outbreak investigation, control measures and the whole genome sequencing (WGS) data of the outbreak isolates. Methods A total of 15 isolates (seven clinical isolates from allogenic stem cell transplant (SCT) recipients and eight wastewater isolates recovered from patients’ toilets) were analyzed by whole genome sequencing. Results Genome based typing identified two clusters of the high risk clones ST167/CT12607 and ST617/CT2791. Long-read sequencing of selected isolates from both clusters identified two different plasmids, however with a highly similar genetic context of the bla NDM-5 containing region. Genomic analysis revealed the presence of additional resistance genes, including bla CTX-M-15, and bla OXA-1, and virulence factors. Four patients were colonized with NDM-5-EC, two patients suffered bacteremia caused by the outbreak strain and two deaths were associated with an NDM-5-EC infection. The outbreak source was traced to toilet sewage pipes, which remained persistently contaminated despite extensive cleaning and disinfection. Successful eradication of NDM-5-EC from the installations required disassembly, hot water pressure washing of the sewage pipes and complete replacement of all movable parts. Additionally, colonized patients were instructed to use wheeled commodes instead of toilets, and a pre-admission screening strategy was implemented for all patients undergoing hematologic stem cell transplantation. The outbreak was successfully terminated in November 2020. Conclusion NDM-5-EC, especially high-risk clones such as ST167 and ST617, can persist in hospital wastewater systems despite cleaning and disinfection efforts and can cause prolonged outbreaks. Therefore, a comprehensive bundle of interventions like the ones applied in our study is essential, especially in clinical settings with heavily immunosuppressed patients.